2007
DOI: 10.2176/nmc.47.383
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Endothelial Injury in Elderly Patients With Severe Head Injury Measured by Serum Thrombomodulin and von Willebrand Factor

Abstract: Elevated serum levels of thrombomodulin (TM) and von Willebrand factor (vWf) are good indicators of injury and activation of cerebral endothelium in patients with severe simple head injury. The present study evaluated cerebral endothelial injury or activation as the serum levels of TM and vWf in elderly and younger patients with similar brain trauma, to evaluate the primary parenchymal injury of the brain. Patients with head injury were classified into the young group (16-30 years), the middle-aged group (31-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Age-related deterioration in cerebrovascular reactivity has been reported as a factor responsible for the poorer outcomes in elderly TBI patients (Czosnyka et al, 2005). Yokota et al (2007) have demonstrated that the serum levels of thrombomodulin and von Willebrand factor as indicators of cerebral endothelial injury and activation are significantly higher in the elderly than in younger patients at the very early phase after severe TBI. They concluded that the higher sensitivity to cerebral endothelial activation and injury in elderly patients will cause a high incidence of delayed intracranial hematoma and poorer outcomes.…”
Section: Age-related Worse Outcome In Tbimentioning
confidence: 99%
“…Age-related deterioration in cerebrovascular reactivity has been reported as a factor responsible for the poorer outcomes in elderly TBI patients (Czosnyka et al, 2005). Yokota et al (2007) have demonstrated that the serum levels of thrombomodulin and von Willebrand factor as indicators of cerebral endothelial injury and activation are significantly higher in the elderly than in younger patients at the very early phase after severe TBI. They concluded that the higher sensitivity to cerebral endothelial activation and injury in elderly patients will cause a high incidence of delayed intracranial hematoma and poorer outcomes.…”
Section: Age-related Worse Outcome In Tbimentioning
confidence: 99%
“…34) As in our elderly patients, such vulnerability might be one of the reasons for long-term impairment of autoregulation and subsequent persistent cerebral hypoperfusion. The level of endothelial damage was higher in elderly patients than in younger patients, so the impairment of autoregulation might persist longer in elderly patients in our study.…”
Section: Discussionmentioning
confidence: 83%
“…showed that poor outcomes after TBI in elderly patients were associated with activation of the cerebral endothelium, as measured by the increased serum levels of thrombomodulin and von Willebrand factor, compared to young and middle-aged patients. [ 43 ] In another study, they also showed that the levels of von Willebrand factor paralleled plasma FDP levels. [ 44 ] These results support the hypothesis that fibrinolytic abnormalities increase in older TBI patients because of the high sensitivity of cerebral endothelial cells to trauma.…”
Section: Discussionmentioning
confidence: 98%